Baguio, Angeles & Olongapo trade directory & tourist guide - Pasion, Francisco Q. publisher & editor-in-chief.; Pasion, Francisco E. managing editor; Canlas, Demetrio G. business manager; David, Florencio E. administrative officer; Villasanta, Ric L. advertising & circulation manager; Umali, Onofre adviser; Bugayong, Joaquin adviser (Manila Francisco Q. Pasion, 1971)
"With this little contribution, the publisher and his staff, hopes to help improve and develop our country's infant Tourist Industry by way of informing and promoting to the outside world, the grandeur, the vast scenic spots, the warm and friendly Filipino Hospitality and the beauty of our country ... "THE PHILIPPINES"."--Foreword
Keywords: Philippines -- Description and travel -- Guidebooks